Microfluidic production of polyacrylic acid functionalized PEG microgels for efficient biomolecular conjugation - Choi, Yoon; Park, Su-Ryeon; Lee, Sei-Jung; Choi, Chang-Hyung (Frontiers in Sensors, 2022)
We present a double emulsion drop-based microfluidic approach to produce uniform polyacrylic acid functionalized polyethylene glycol (PAA-PEG) microgels. By utilizing double emulsion drops as templates, we produce monodisperse microgels by rapid photopolymerization of the inner prepolymer drop consisting of polyacrylic acid (PAA) and polyethylene glycol diacrylate (PEGDA), followed by dewetting the oil layer when they disperse into an aqueous media. The size control of the PAA-PEG microgels with a broad range is achieved by tuning the flow rate of each phase; the uniformity of the microgels is maintained even when the flow rate changes. The results show rapid R-phycoerythrin (R-PE) coupling with the microgels’ carboxylate with minimal non-specific adsorption, demonstrating highly efficient and reliable biomolecular conjugation within PAA-PEG microgels.